Moving Up the Ladder : Poverty Reduction and Social Mobility in Nepal - World Bank Group (World Bank, Kathmandu, 2016)
Nepal is emerging from a series of crippling shocks. Barely recovered from the devastation and loss wreaked by the earthquakes in April 2015, the country experienced a near total economic seizure between September 2015 and January 2016 as cross-border trade with India came to a halt. The shortages of fuel, raw materials and other essential commodities caused prices to soar, businesses to curtail operations and the economy to register the lowest growth experienced in the last fourteen years. This report attempts to contribute by deepening the understanding of the key elements of the processes that have driven improvements in living standards and identify some of the challenges that lie ahead. This report also performs a careful analysis of the levels as well as the trends in inequality in last two decades in an attempt to understand the economic underpinnings of the demand for inclusion that has so fundamentally shaped Nepal’s contemporary socio-political landscape. Finally, this report also presents some novel insights on social and economic mobility experienced by Nepalis across generations as well as over a lifetime.